Studi Komparasi Sistem Hubungan Industrial dalam Ekonomi Konvensional dan dalam Ekonomi Islam - Pratiwi, Aidha Mega; Pertiwi, Ajeng Putri; Fahmi, Muhammad Iqbal; Zulfikar, Muhammad Refki (Diponegoro Journal of Islamic Economics and Business, 2022)
Indonesia’ level of financial inclusion and literacy index in the Islamic capital market is quite slow for around 0,022% and 0,01% eventhough Indonesia is a country with largest Muslim majority (85% o population). Furthermore, the fact shows that Indonesia is the country with the 4th highest grwoth in the capital market industry in Asia-Pacific throughout 2017. The potential for growth and development of Islamic capital market in Indonesia is very high, but not followed by the growth rate of financial literacy and inclusion index especially in the capital market sector. The aim of this paper is to identify a new strategic approach that is applicable to increase Islamic financial literacy and inclusiveness in terms of Islamic capital market. This study uses a qualitative method with literature from journal articles, government reports, news, and others in reviewing, identifying, and knowing the strategies o be implemented. The result shows that there were six specific strategies used in increasing the literacy index and inclusion index of Islamic capital market, namely, rebranding negative investment stereotypes, building sustainable promotions and campaigns through offline and online platforms, creating an integrated online market for capital market product.